Flight Tests of Autopilot Integrated with Fault-Tolerant Control of a Small Fixed-Wing UAV - Shuo Wang (Mathematical Problems in Engineering, 2016)
A fault-tolerant control scheme for the autopilot of the small fixed-wing UAV is designed and tested by the actual flight experiments. The small fixed-wing UAV called Xiang Fei is developed independently by Nanjing University of Aeronautics and Astronautics. The flight control system is designed based on an open-source autopilot (Pixhawk). Real-time kinematic (RTK) GPS is introduced due to its high accuracy. Some modifications on the longitudinal and lateral guidance laws are achieved to improve the flight control performance. Moreover, a data fusion based fault-tolerant control scheme is integrated in altitude control and speed control for altitude sensor failure and airspeed sensor failure, which are the common problems for small fixed-wing UAV. Finally, the real flight experiments are implemented to test the fault-tolerant control based autopilot of UAV. Real flight test results are given and analyzed in detail, which show that the fixed-wing UAV can track the desired altitude and speed commands during the whole flight process including takeoff, climbing, cruising, gliding, landing, and wave-off by the fault-tolerant control based autopilot.